"Titta, jag ser dig!" - kameran som resurs för delaktighet i förskolan - Lena O Magnusson; Karin Forsling; Kristina Walldén Hillström (Dalarna university, 2023)
This article contributes knowledge concerning how the use of cameras as a digital resource can offer children participation and agency in the everyday education practice of preschool. The data is retrieved from three different research studies, and the analytical approach focuses on children's interaction with cameras as a photographic and cinematic resource. The data is analysed following multimodality (Goodwin, 2000; Jewitt, 2014) and using a participation model (Szönyi & Söderqvist Dunkers, 2020). The analyses carried out are based on re-analyses of previously produced data. Theoretically, the study is contextualised within the sociology of childhood, where one of the basic assumptions is that children are regarded as co-constructors with opportunities and abilities to independently act, interpret and reinterpret their lives (Corsaro, 2018). The results show that children's interaction with cameras as a digital resource enables participation in everyday practice from several aspects. Children's agency and participation become visible in the children's interaction with the camera function and between children and children, children and educators, where laughter, gazes, gestures, silence and the development of digital competence are part.